Wife abuse in Bangladesh : an unrecognised offence - Ameen, Nusrat (Dhaka : The University Press, 2005)
Includes bibliographical references (p. [143]-148) and index.
Altab
Keywords: Wife abuse -- Bangladesh; Abused wives -- Legal status, laws, etc. -- Bangladesh